TVRI Stasiun Riau Kepri: Studi Kasus Keberadaan Media Massa dalam Pembangunan Provinsi Riau (1998-2018) - Raiza Nanda Pratama; Ahmal; Asyrul Fikri (Jurnal Pendidikan Sejarah, 2021)
Abstract: Today, mass media development is growing rapidly, this can be seen in the variety of choices for people to get news, entertainment and knowledge. One of the growing mass media is television. Television plays a very important role in development. The purpose of this document is: To understand the initial process of the formation and development of the Riau Kepri Station of the Television Republic of Indonesia (TVRI) and the role of the Riau Kepri Station of the Television Republic of Indonesia (TVRI) as a mass media in development. Province of Riau in the field of Social and Economic, Education and Culture. The research method that will be used in this research is the historical method. The television era in Riau province started since 1977 when the TVRI Relay Station Tower was built at that time. The development of TVRI Riau Kepri Station began to appear in 1999, where in 1999 TVRI Riau Station was able to broadcast locally for the first time, exactly in January. The role of TVRI Riau Kepri Station served as a tool used to disseminate information about the public's development. in the province of Riau.